Transperitoneal Calcium Balance in Anuric Continuous Ambulatory Peritoneal Dialysis and Automated Peritoneal Dialysis Patients - Chieko Hamada; Yasuhiko Tomino (International Journal of Nephrology)
Backgrounds. Calcium (Ca) and bone metabolism in continuous ambulatory peritoneal dialysis (CAPD) and hemodialysis (HD) patients show a remarkable difference depending on dialysis modalities. The levels of serum Ca and phosphate (P) in HD patients fluctuate contributing to the intermittent and rapid removal of plasma solute unlike in CAPD. Characteristics of plasma solute transport in automated peritoneal dialysis (APD) patients are resembled with that in HD. The purpose of the present study was to examine the difference of transperitoneal Ca removal between APD and CAPD anuric patients. Subjects and Methods. Twenty-three APD anuric patients were enrolled in this study. Biochemical parameters responsible for transperitoneal Ca removal in 24-hour and 4-hour peritoneal effluents were analyzed on CAPD and APD. Results. Transperitoneal Ca removal on APD was smaller compared with that on CAPD. The Ca removal was related to the ultrafiltration during short-time dwell. Decrease of the Ca removal during NPD induced by short-time dialysate dwell caused negative or small Ca removal in APD patients. The levels of intact PTH were increased at the end of PET. Conclusion. It appears that short-time dwell and frequent dialysate exchanging might suppress the transperitoneal Ca removal in anuric APD patients.